AWAKE XIFOPUBIC LAPAROTOMY FOR DESMOID TUMOR DURING PREGNANCY – A CASE REPORT - Silva, Mafalda (2023)
Non obstetric surgery during pregnancy is rare with maternal malignancy being one of the most common causes. Sporadic pregnancy related desmoid tumours are even more uncommon and optimal management of this tumour is complex. Complete surgical excision is the most commonly accepted treatment. Surgery during pregnancy is challenging as it demands taking into consideration requirements for both the mother and the foetus. The choice of anaesthetic plan must take into account surgical and patient specificities, and the effects of anaesthesia on the foetus. We report the perioperative management of a pregnant woman in the second trimester of pregnancy who underwent complete excision of a desmoid tumour under regional anaesthesia. Intraoperative change of surgical plan posted an additional challenge.